ANALISIS EFISIENSI MODEL BILAH HORIZONTAL AXIS WIND TURBINE DAN VERTICAL AXIS WIND TURBINE NACA 6510 UNTUK KECEPATAN ANGIN 3M/S - 12M/S - Muhammad Daffa Aly, (2020)
Energy demand in this world continues to increase, this happened because of population growth, economic growth and energy usage is increasing over by time. Wind energy is a solution of alternative energy and renewable energy, with consolidation that wind is an unlimited and environmentally friendly natural resources. A comparation between horizontal and vertical wind turbines shows an efficiency Cp (Coefficient of power) of two difference turbines with variation of speeds 3m/s, 6m/s, 9m/s and 12m/s. So, that can be known that horizontal and vertical wind turbine have an optimal Cp in each variation of wind speed. These results will be using by several simulations. The simulation results are done with QBlade and Ansys software, at speed of 3m/s QBlade data between horizontal and vertical obtained optimal Cp is rated 0.935145 for vertical. At speed of 6m/s QBlade data between horizontal and vertical obtained optimal Cp rated 0.158268 for horizontal. At speed of 9m/s QBlade data between horizontal and vertical obtained an optimal cp rated 0.22601127 for horizontal. At speed of 12m/s QBlade data between horizontal and vertical obtained an optimal Cp rated 0.544217 for horizontal.